IJCM_310A: Active Case Finding for Tuberculosis in outreach centres of a medical college in Puducherry, India: A Mixed Methods Study on Outcomes and Implementation Challenges - Navilson Binoth E; Konduru Rajesh Kumar (Wolters Kluwer Medknow Publications, 2024)
Background: Tuberculosis is the leading cause of death from a curable infectious disease and is responsible for 9.9 million new cases and 1.3 million deaths. Over 95% of TB deaths occur in low and middle-income countries. The WHO TB statistics for India for 2021 give an estimated incidence figure of 2,590,000 million cases. In Puducherry, 4500 cases were notified in the same year, with a TB notification rate of 226 per lakh population. ACF has potential benefits but also challenges, which need to be carefully assessed when developing and implementing ACF policies. Objectives: 1) To understand the experiences of healthcare workers during the implementation of Active Case Finding (ACF) activities 2) To assess the implementation of ACF using the feasibility indicators. Methodology: Qualitative interviews (IDI & FGD) were conducted among healthcare workers (Nodal Officers, Medical Officers, and Medical Interns) involved in the ACF to enumerate their experiences during the survey and the implementation challenges they faced. Additionally, a set of feasibility indicators from the literature (Hemant et al.2023) was identified to assess the implementation of ACF in outreach centres of a medical college in Puducherry. Results: Three overarching themes emerged through qualitative interviews: awareness of ACF and TB, implementation challenges, and mechanisms to overcome the challenges. Feasibility indicators will be elicited upon completion of data curation and analysis. Conclusion: The intricate details involved in the implementation of ACF would be understood through the experiences of Health Care Workers as well as quantitative estimation of ACF implementation.